Correlation between treadmill acceleration, plantar pressure, and ground reaction force during running - Lee, A. J. Y.; Chou, J. H.; Liu, Y. F.; Lin, W. H.; Shiang, T. Y. (The Engineering of sport 7, Volume 1, 2008)
The purpose of this study was to investigate the correlation between peak tread-mill acceleration (PTA), peak plantar pressure (PPP) and peak ground reaction Force (PGRF) during running. Eight active College students (mean age: 21 ± 0.8 yrs; height: 169.9 ± 7.4 cm; weight: 62,5 ± 9.8 kg) wore standardized shoes and ran on a speed calibrated treadmill (95Te, Life Fitness, USA) at seven speeds (1.3,1.8,2.2,2.7,3. 1, 3.6, and 4.0 m/s). PTA was measured by a dual axis accelerometer (MAX2312G/M, MEMSIC, Inc, USA) which plugged into the middle of the treadmill running board, with an MP100 data acquisition System (BIOPACK Systems, Inc, USA). In-shoe PPP and PGRF were measured by a wireless foot pressure measuring System (F Scan Mobile, Tekscan, USA). The PTA, PPP, and PGRF data were recorded for 10 seconds at a sampling rate of 500 Hz for each running speed. PPP and PTA data at different speeds were compared across the range of speeds by a repeated measures one-sample t-test. A Standard linear least squares correlation was used to calculate the coefficients of determination (r2) between PTA, PPP, and PGRF. The running speed had a different effect on PTA, PPP, and PGRF at the seven speeds. The PTA, PPP, and PGRF during the fastest speeds (4.0 m/s) increased approximately 425% (2.2 g vs. 0.53 g), 216% (225.7 psi vs. 104.4 psi), and 228% (311.2 kgs vs. 136.6 kgs), respectively, when compared to the slowest speed (1.3 m/s). The coefficients of determination between PTA and PPP, PTA and PGRF, PPP and PGRF were 0.75, 0.78, and 0.91, respectively (p<.05). The PTA, PPP, and PGRF increased linearly with faster running speed and were strongly correlated with each other. This study demonstrates that an onboard treadmill accelerometer could be used to estimate the PPP and PGRF during running.